Forming Leaders for the Public Church: Vocation in Twenty-First Century Societies - Deressa, Samuel Yonas; Dreier, Mary Sue (Lexington Books, 2023)
These challenging times demand that Christian churches and their leaders faithfully and effectively address diverse global situations with Gospel-rooted compassion and justice. These essays argue that public theology provides the trinitarian theological framework which fuels wise and compassionate public participation in God's mission within the world today. Public church leaders from the Global South and Global North join their voices to explore the global implications of public theology within unique situational particularities. Their essays are principally based on the public theology and theological commitments of Gary M. Simpson, Lutheran pastor and systematic theologian. Simpson's public theology is an intersection of Lutheran theology, post-colonial approaches to missiology, the growing field of congregational studies, and the Civil Society turn in Critical Social Theory. Expanding on various aspects of Simpson's public theology, these essays provide a glimpse of newly-emerging global public theology with leadership implications for twenty-first century contexts. This book calls the church to bear today's multi-dimensional crises with courage, mutuality and cooperation. Congregations who seek to participate in God's mission by confronting these challenging realities will find encouragement through the theological reflections, first-hand experiences, and innovative public leadership narrated in these essays.